The Effect of Limited Liability on the Informativeness of Earnings: Evidence from the Stock and Bond Markets* - PLUMMER, C. ELIZABETH; TSE, SENYO Y. (Contemporary Accounting Research, 1999)
Abstract Previous empirical research on the informativeness of earnings has focused on stockholders, and has not examined differences in earnings' informativeness for stockholders and bondholders. Because stockholders are residual claimants and bondholders are fixed claimants, the informativeness of earnings should differ for these two types of investors. When a firm's default risk is low, changes in its financial condition should be of limited relevance to bondholders, but should be relevant to stockholders. In contrast, as the likelihood of financial distress increases, stockholders' limited liability allows them to abandon the firm to the bondholders (Fischer and Verrecchia 1997). Accordingly, as a firm's default risk increases, changes in its financial condition should be increasingly important to bondholders and less important to shareholders. Because earnings provide information on firm value, the stock return‐earnings association should decrease as the firm's financial strength declines, while the bond return‐earnings association should increase. We use two measures of a firm's financial strength: the firm's bond rating and its reporting of a loss. Consistent with our hypotheses, we find that the association between stock returns and changes in annual earnings decreases as bond ratings decline, while the association between bond returns and changes in annual earnings increases. These results suggest that as the company's financial condition deteriorates, earnings become less relevant for stock valuation and more relevant for bond valuation. When we partition firms based on their loss status, we find a stronger association between stock returns and annual earnings changes for firms with positive earnings (profit firms) than for firms with losses, consistent with earlier studies. In contrast, we find that the association between bond returns and earnings changes is greater for loss firms than for profit firms. These results suggest that losses reduce the informativeness of earnings for stockholders but increase informativeness for bondholders, suggesting that investors view losses as indicating increased credit risk.